Using a Digital Multimodal-Google Sites to Enhance Students' Reading Comprehension Proficiency in Narrative Text - Muhammad Sholahuddin; Setia Rini (PANYONARA: Journal of English Education, 2025)
This study discusses students' challenges in reading narrative texts. In this study, we have discussed the effectiveness test of the Google Sites digital multimodal platform to improve students' comprehension in reading. This study used pre-experimental approach with a single-group pretest-posttest design. The subjects of this study were 79 ninth-grade students at SMP Ma’had Islam Semarang. They were selected using purposive sampling. In this method. Iit systematically explored basic comprehension through pretests, intervened students using Google Sites, and ended with a posttest to determine the improvement in reading comprehension achieved by students. The main findings of this study show an increase in students' understanding in reading narrative texts through the Google Sites digital multimodal platform. So it can be concluded that Google Sites' learning tools are significant for improving the reading comprehension of narrative texts. The limitation of this study is the absence of a control group, but the results of the study show that this method approach is highly recommended to maximize students' reading comprehension instruction.